ANALISIS CUSTOMER RELATIONSHIP MANAGEMENT DALAM MEMPERTAHANKAN LOYALITAS PELANGGAN PADA JASA PENGIRIMAN CARGO - Gusti Ayu Alit Cantika Dewi; Putu Dyah Permatha Korry; Anak Agung Mia Intentilia; I Gusti Agung Ananda Putra (Journal of Innovation Research and Knowledge, 2025)
Increasingly fierce competition in the cargo delivery service industry requires companies to focus not only on service quality, but also on managing long-term relationships with customers. This study aims to analyze the implementation of Customer Relationship Management (CRM) in building customer relationship quality and its implications for customer loyalty at PT. Tirta Mitra Utama Cargo. This study uses a qualitative approach with a descriptive research type. Data was obtained through in-depth interviews, observations, and documentation of management, operational staff, and selected customers using purposive sampling techniques. Data analysis was conducted using the Miles and Huberman interactive model through the stages of data collection, data reduction, and conclusion drawing. The results show that the implementation of CRM at PT. TMU Cargo has been carried out at the operational level, but it has not been structured and integrated optimally in accordance with Payne and Frow's five core CRM processes, namely strategy development, value creation, multi-channel integration, information management, and performance evaluation. These CRM practices shape the quality of customer relationships, which are reflected in communication skills, company commitment, and customer trust. Responsive and personalized communication is the company's main strength, while limitations in customer data management, information consistency, and performance evaluation have an impact on customer loyalty, which is not yet optimal. This study concludes that a more systematic strengthening of CRM is needed to improve the quality of customer relationships and maintain loyalty in the context of cargo delivery services